2021
DOI: 10.3390/genes12101607
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Role of Common and Rare Variants in a Large Italian Multiplex Family of Multiple Sclerosis Patients

Abstract: Known multiple sclerosis (MS) susceptibility variants can only explain half of the disease’s estimated heritability, whereas low-frequency and rare variants may partly account for the missing heritability. Thus, here we sought to determine the occurrence of rare functional variants in a large Italian MS multiplex family with five affected members. For this purpose, we combined linkage analysis and next-generation sequencing (NGS)-based whole exome and whole genome sequencing (WES and WGS, respectively). The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Despite GWASs explaining that there are common SNPs associated with various diseases, known common variants only account for part of the estimated heritability of common complex diseases. Nadia et al identified the rare functional variants analyzed within a large Italian MS multiplex family with five affected members [ 58 ]. Another recent study showed that up to 5% of MS inheritability may be accounted for by rare variations in the gene coding sequence, with four novel low genes driving MS risk independently of common variant signals [ 59 ].…”
Section: Gene Risk and Signaling Pathwaymentioning
confidence: 99%
“…Despite GWASs explaining that there are common SNPs associated with various diseases, known common variants only account for part of the estimated heritability of common complex diseases. Nadia et al identified the rare functional variants analyzed within a large Italian MS multiplex family with five affected members [ 58 ]. Another recent study showed that up to 5% of MS inheritability may be accounted for by rare variations in the gene coding sequence, with four novel low genes driving MS risk independently of common variant signals [ 59 ].…”
Section: Gene Risk and Signaling Pathwaymentioning
confidence: 99%
“…However, previous studies have not explored the tumor suppressor function of CYP26B1 in ESCC in vivo. Moreover, some studies have found that the rare or low‐frequency risk variants usually function collectively with common variants by affecting one susceptibility gene or pathway 18,19 . Therefore, whether there are common variants that may influence the occurrence of ESCC via affecting the function of CYP26B1 need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon can be explained in different ways, including a poor representation of rare variants in typed arrays, epigenetic mechanisms and interaction between genetic and environmental factors, whose role can be better explored in family-based studies that offer a privileged setting of higher prevalence of the disease. This strategy allowed the identification of several rare variants with a possible role in MS susceptibility [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], and several genes were implicated, such as TYK2 [ 15 ], also confirmed in sporadic case [ 4 ], UBR2 and DST [ 11 ], and more recently, among others, MBP, MECP2, and CPT1A [ 13 ].…”
Section: Introductionmentioning
confidence: 99%